Twenty-one Days of Solitude - Prabhakar, Hemanshu (Indian J Crit Care Med, 2021)
As the world is now gradually coming out of the “lockdown” phase, one can expect a change in the demographics and epidemiology of trauma. With traffic back on roads and shifting life again towards “normalcy”, it is imperative to carry out introspection and see how we can stop trauma from reaching its pre-COVID levels. How to cite this article: Prabhakar H. Twenty-one Days of Solitude. Indian J Crit Care Med 2021;25(3):249–250.